MENYINGKAP NILAI KEADILAN (DALAM PERSPEKTIF SYARI’AH ISLAM) YANG TERKANDUNG DI DALAM GOOD CORPORATE GOVERNANCE - Anis Wulandari (Universitas Trunojoyo Madura, 2010)
This research aimed to know the presence and the form of justice values in Good Corporate Governance (within Islam perspective). However according to OECD; Good Corporate Governance in a whole principles has been reflecting those values, although in some extent its different. Of course, its because built with different based formulation other than Islam’s values, or even far from its.In order to have those five principles more close to the Islam characters; first, by internalized “tauhid” in the Islam principles on OECD point of view, second, by framing Good Corporate Governance principles on OECD version with justice values that build in the Islam’s syariah. In conclusion, for reforming OECD version about Good Corporate Governance to the more in Islamic principles and having justice values in Islamic point of view, injecting the main source of one paradigm that ALLAH is the creator of the universe to those five principles is the best solution.